Books that help and books that hinder - Thackrey, Cora G. (My University, 1898)
Introduction: “In one sense,” says Andrew Sang, “there are no books that do not help a man, and in another, it may be doubted whether any books help him at all.” He goes on to say that every book that can be read will please, amuse, interest, divert, or at least occupy the time, and in that sense is helpful; but he does not think any book (excepting the sacred literature) can be of any help in the great problems of life, except by way of sympathy. Marcus Aurelius himself, he declares, can say no more than to “endure and abstain.” Books cannot give us courage, strength of character, and patience endure; they cannot make us grieve the less or rejoice the more, except by the comforting quality, sympathy, or the force of example. But can anything except God himself give us more than this? Our joys, our grief’s, are for us alone to experience; in ourselves alone must be the strength and power; with the sympathy of friends to sustain, with the example of others to point out the way, and with God’s help; to fight the battles of life and conquer, or else life must be a failure so far as we are concerned.
Citation: Thackrey, Cora G. Books that help and books that hinder. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Marcus Aurelius; Literature; Books; God; Theses; Manuscripts (documents)